Modelling the dynamics and control system of hybrid airship UAV (HAU-3) - Sedan, Mohd Fazri (2022)
In this thesis, a 3.3 m length, finless hull airship called HAU-3 is presented. Four vector thrusters arranged in H-Frame configurations were attached to the hull, which enable the airship to maneuver in 5DOF. To allow a deeper understanding of the HAU-3 motion behavior and to design a flight controller, a reliable dynamics model representation and simulator of HAU-3 are developed. A six-degrees of freedom (6DOF) non-linear mathematical model representation is constructed using the Newton-Euler approach. The dynamics model parameters were identified via semi-empirical, computer-aided modelling (CAD) and experimental approaches. The HAU-3 dynamics model was then integrated into Simulink and MATLAB to construct a closed-loop simulator to analyze the airship's behavior. Five separate Proportional, Integral and Derivative (PID) controllers were designed using the developed non-linear dynamic model. A series of indoor static tests and outdoor flight tests were conducted to evaluate the controller performance and to validate the simulator response. A dynamic response model of the vector thrusters developed provides excellent agreement with the actual thrust and motor transient response with 0.29 s delay and 0.2 N steady-state error. The indoor static test of the yaw controller shows an adequate yaw state change tracking performance with a 9.5% average difference in maximum overshoot and approximately 30% settling time difference by comparison of actual and simulated responses. The controller is able to suppress the pendulum oscillation in pitch and roll with 0.165 Hz and 0.3 Hz oscillation frequency, respectively and at least 20°maximum angle deviation. The altitude controller also shows an excellent performance in tracking the change in altitude during outdoor flight tests with an average 0.5 m altitude difference between simulation and actual recorded altitude. The developed HAU-3 simulator provides a reasonable estimate of the airship's attitude and translational states for modelling and simulation purposes.